2008
DOI: 10.3174/ajnr.a1001
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion Tensor Imaging in Chronic Subdural Hematoma: Correlation between Clinical Signs and Fractional Anisotropy in the Pyramidal Tract

Abstract: BACKGROUND AND PURPOSE: Diffusion tensor imaging (DTI) was introduced as a good technique to evaluate structural abnormalities in the white matter. In this study, we used DTI to examine anisotropic changes of the pyramidal tracts displaced by chronic subdural hematoma (CSDH).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
1
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 20 publications
0
26
1
2
Order By: Relevance
“…2,14,15,24 Yokoyama et al 15 reported that the mean FA ratio in the affected pyramidal tract decreased 11% compared with that in the unaffected side among the good-recovery group. In contrast, the mean Fig 1.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2,14,15,24 Yokoyama et al 15 reported that the mean FA ratio in the affected pyramidal tract decreased 11% compared with that in the unaffected side among the good-recovery group. In contrast, the mean Fig 1.…”
Section: Discussionmentioning
confidence: 99%
“…The cutoff point of the rFA that divides the 2 groups is set at 0.85. the corticobulbar tract. 15 The corticospinal tract is a large and highly anisotropic tract; on the other hand, the corticobulbar tract is easily affected by other fibers running in the anteroposterior projection. 29 Moreover, the pyramidal tract does not run precisely perpendicular to the axial plane.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, DTI FA measurement is compromised by interstitial fluid content. 3,5,17,18 The DTI measurement becomes ambiguous in the presence of hemorrhage and edema (FA decreases when there is an increase in interstitial fluid or loss of axons). In contrast, our high angular resolution tracking technique, HDFT, has the ability to both localize and quantify axonal damage at the level of detail necessary for clinical purposes and is robust to changes in white matter pathway shape, interstitial fluid, and stochastic reseeding of the fiber tracks.…”
Section: Discussionmentioning
confidence: 99%
“…Magnetic resonance diffusion tensor imaging (DTI) is currently the only non-invasive method used to assess the structure, morphology and function of WM fibers in vivo (8,9). DTI technology has been widely used in research of the central nervous system.…”
Section: Introductionmentioning
confidence: 99%